2020
DOI: 10.3389/fnagi.2020.588958
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Irisin in Ischemic Stroke

Abstract: Irisin is a PGC-1α-dependent myokine that causes increased energy expenditure by driving the development of white adipose tissue into brown fat-like tissue. Exercise can improve irisin levels and lead to its release into the blood. In ischemic stroke, neurons are always sensitive to energy supply; after a series of pathophysiological processes, reactive oxygen species that are detrimental to cell survival via mitochondrial dysfunction are generated in large quantities. As a protein associated with exercise, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 87 publications
0
13
0
1
Order By: Relevance
“…Recently, the anti-inflammatory, anti-apoptotic and anti-oxidative properties of irisin have received a great deal of attention in various diseases [ 22 ]. Previous studies explored the critical role that irisin played in ischemic stroke in mice models, indicating that irisin can upregulate the levels of brain-derived neurotrophic factor (BDNF) and protects nerve cells from injury during ischemic stroke [ 46 , 47 ]. Clinical investigations revealed that decreased serum concentration of irisin is associated with poor functional outcomes and post-stroke depression in ischemic stroke patients [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the anti-inflammatory, anti-apoptotic and anti-oxidative properties of irisin have received a great deal of attention in various diseases [ 22 ]. Previous studies explored the critical role that irisin played in ischemic stroke in mice models, indicating that irisin can upregulate the levels of brain-derived neurotrophic factor (BDNF) and protects nerve cells from injury during ischemic stroke [ 46 , 47 ]. Clinical investigations revealed that decreased serum concentration of irisin is associated with poor functional outcomes and post-stroke depression in ischemic stroke patients [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most significant roles of irisin include browning of white adipocytes, neural proliferation, and bone metabolism [ 3 , 37 , 38 ]. Other effects of irisin involve glucose homeostasis and cardiac metabolism, which are still under investigation [ 4 ].…”
Section: The Role Of Irisin In Human Pathophysiologymentioning
confidence: 99%
“…Под действием UCP1 повышается экспрессия мозгового нейротрофического фактора (brain-derived neurotrophic factor, BDNF) [17]. Показано, что введение irisin, высвобождение которого провоцируется снижением температуры, уменьшает объем инфаркта мозга у крыс после окклюзии среднемозговой артерии, стабилизирует гематоэнцефалический барьер и стимулирует накопление BDNF, уменьшает объем повреждений миокарда и легких после тотальной остановки кровообращения [18][19][20].…”
Section: молекулярные механизмы низкотемпературных технологийunclassified